2020
DOI: 10.3389/fpls.2020.00245
|View full text |Cite
|
Sign up to set email alerts
|

The Q-System as a Synthetic Transcriptional Regulator in Plants

Abstract: A primary focus of the rapidly growing field of plant synthetic biology is to develop technologies to precisely regulate gene expression and engineer complex genetic circuits into plant chassis. At present, there are few orthogonal tools available for effectively controlling gene expression in plants, with most researchers instead using a limited set of viral elements or truncated native promoters. A powerful repressible-and engineerable-binary system that has been repurposed in a variety of eukaryotic systems… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 33 publications
0
21
0
Order By: Relevance
“…Finally, in organisms such as Anopheles and Aedes mosquitoes, the Gal4/UAS system has encountered limitations due to poor activity (Lynd and Lycett, 2012). Tools employing the Q System, such as HACK, may prove generalizable to more organisms (Matthews et al, 2019; Persad et al, 2020; Riabinina et al, 2016; Subedi et al, 2014; Wei et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, in organisms such as Anopheles and Aedes mosquitoes, the Gal4/UAS system has encountered limitations due to poor activity (Lynd and Lycett, 2012). Tools employing the Q System, such as HACK, may prove generalizable to more organisms (Matthews et al, 2019; Persad et al, 2020; Riabinina et al, 2016; Subedi et al, 2014; Wei et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…A new plant orthogonal regulatory system was recently reported that leveraged a yeast transcriptional regulator to induce synthetic activators or repressors (Belcher et al ., 2020). Such a system or a new synthetic Neurospora‐based 'Q‐system' (Persad et al ., 2020) could be coupled with designed synthetic promoters to tune signal specificity and sensitivity in plants.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps the only phenylpropanoid-related biosensor tested in plants, the Q-system derived from the fungus Neurospora crassa was adapted in Nicotiana benthamiana and soybean ( Reis et al, 2018 ; Persad et al, 2020 ). The Q-system consists of a transcriptional activator (QF) and its repressor (QS); the ligand, quinic acid, binds to QS to relieve the repression.…”
Section: Phenylpropanoid Biosensorsmentioning
confidence: 99%